A Study on Electrolyte Abnormalities in Patients with Chronic Kidney Disease - Jothilakshmi.R , Jothilakshmi.R; T. P, Oviya.; Aswini.R, Aswini.R (Journal of Neonatal Surgery, 2025)
BACKGROUND: Electrolytes are naturally occurring elements and compounds that play a crucial role in regulating key physiological functions. Electrolyte replacement becomes essential in cases of prolonged vomiting, diarrhea, or after intense physical activity. Commercial electrolyte solutions are readily available, especially for treating sick children. An electrolyte panel, also known as a serum electrolyte test, is a blood test used to measure the levels of the body’s major electrolytes. These substances are found in the blood, body fluids, and urine. AIM: The aim of this study is to evaluate serum electrolyte abnormalities in chronic kidney disease (CKD) patients to assess the severity of the condition. MATERIALS AND METHODS: Collect the serum blood samples for the above 20 years included in this study. And a comparison of men and women in age categories. The blood samples were drawn from the CKD patients. The samples are analyzed by the Elyte 5i semi-auto analyzer machine for electrolytes (sodium, potassium, and chloride). RESULT: Out of 100 blood samples collected, abnormalities of electrolytes (sodium, potassium, chloride) were found in 50 patients, and 50 were in the control group. The abnormalities of electrolytes lead to many disorders: hypernatremia, hyponatremia, hyperkalemia, hypokalemia, hyperchloremia, and hypochloremia. There is no significant association between gender and electrolytes, sodium (p=0.42), potassium (p=0.53), or chloride (p=0.216). CONCLUSION: The present study concluded that increased or decreased electrolytes lead to severe complications. The blood samples were collected for above 20 years of age including. There is no significant association between gender and electrolytes for sodium, potassium, and chloride